Research priority-setting: reproductive health in the occupied Palestinian territory - Niveen M. E. Abu-Rmeileh; Rula Ghandour; Marina Tucktuck; Mohammad Obiedallah (BMC, 2018)
Abstract Background Occupied Palestinian territory (oPt) is an authority with limited resources. Therefore, research conducted in such a setting should be prioritized and coordinated to follow a national research agenda. This study aims to produce a research agenda for reproductive health in the oPt that can be utilized by reproductive health stakeholders and contribute to the development of policy-based evidence to guide health practice. Methods In the current study, we followed research prioritization methods developed by the World Health Organization-Child Health and Nutrition Research Initiative. Research questions were obtained from reproductive health experts in the oPt. The questions were then grouped into thematic areas which were prioritized by the reproductive health experts. Scores were calculated and sorted to define the top priority research areas. Results A total of 232 research questions were prioritized by 30 reproductive health experts. Health system issues were the most addressed in the top 50 research questions. They included questions on the quality of services and health professionals' knowledge and continuous professional training. Adolescents' sexual and reproductive health and gender-based violence were rarely mentioned in the top 50 questions. The number of questions related to safe motherhood was around 50% followed by questions related to health system. Questions related to elderly women and menopause as well as reproductive system cancers were also within the top 50 ranked questions. Conclusions Priority research areas in reproductive health were identified for the oPt, which should be utilized by researchers with a focus on the high priority areas. Policy makers and funders should coordinate their efforts to ensure the production of research with value to the Palestinian context, in the most efficient way possible.